Case Report: IVCM of corneal chlorpromazine toxicity drug deposits - Xiao, Xianwen; Fang, Xie; Xie, Zhiwen; Luo, Shunrong; Lin, Yuan; Wu, Huping (Frontiers in Medicine, 2025)
To investigate corneal deposits in a patient undergoing long-term chlorpromazine therapy using in vivo confocal microscopy with the HRT II Rostock Corneal Module. We reported a 45-year-old woman with a 7-year history of chlorpromazine therapy presented with bilateral photophobia and a 4-year history of gradual-onset blurred vision. Slit-lamp examination revealed yellowish deposits in the corneal endothelium and Descemet’s membrane. In vivo confocal microscopy identified irregular hyper-reflective deposits in all corneal layers. The epithelial and superficial stromal deposits had well-defined edges, while the posterior stromal, Descemet’s membrane, and endothelial deposits appeared as hollow granules and streaks. This study is the first to use in vivo confocal microscopy to identify crystalline deposits in the corneal stroma and endothelium caused by high-dose chlorpromazine. These findings offer new insights into drug metabolism on the ocular surface and provide a basis for future research.